Avaliação do comportamento reológico e colorimétrico de chocolates - Nacano, Evelin Thais (2013)
Chocolate is a product known worldwide and its production varies according to the local culture and preference of its consumers. The study of the rheological behavior and colorimetric assay is essential to get efficiency in processes of dimensioning, reduction of expenses with formulations and preparation of the product. In This way, this work aimed to study and evaluate the parameters and rheological additives and colorimetric commercial chocolate milk and half-bitter, marketed in Campo Mourão - Parana, with purpose to observe these behaviors in finished products and greater output to consumers. The rheological analysis was performed in a reometer Brookfield LVDV III, causing a growing curve from 0.01 to 35 s-1 and decreasing from 35 to 0.01 s-1, in duplicate, that for each curve was obtained ten points of shearing tension versus shear rate, totaling 20 points. The rheological behavior was analyzed according to the Model of rheological Law of Power by software ORIGIN 7.0 (OriginLab Corporation, Ma, USA), where the coefficient of determination (R2) was analyzed to check the quality of the fit of the results in the model used. The experimental data adjusted well to the model law of power (high values of R2). The samples of chocolates presented a behavior non-newtonian pseudoplastic behavior. Through the analysis of thixotropy, it was possible to verify that the samples of chocolate have hysteresis when shear. For the analyzes, the colorimetric parameters brightness (L*) and chromaticity from green to red (a*) and from blue to yellow (b*) were scanned by portable colorimeter Hunterlab Miniscan XE Plus in triplicate, in three distinct points of slabs of samples. It was extracted the mean values of the results and the standard deviation of each parameter, where it was found that for the brightness (L*) values obtained are closer to the dark zone (black) from that of the clear zone, because on a scale of zero to 100, the parameter L* reached values smaller than 50, being characterized dark. For the parameters of chromaticity a* and b*, the values obtained were positive while in regions of red and yellow, resulting in brown coloring characteristic of chocolate.